Automated estimation of urinary calcium using the Eppendorf flame photometer - Bold, A. M. (1966)
A method is described for estimating urine calcium on a mechanized Eppendorf flame photometer with twin channels at a rate of 60 per hour. Sodium is estimated simultaneously so that a correction can be made for the small sodium error. Errors due to potassium and phosphate are minimized by adding these ions to the standards and to the diluting fluid. Results agree well with those obtained by Trinder's naphthal-hydroxamic acid precipitation method.